A pseudo-transient heat transfer simulation of a continuous casting process, employing the element-free Galerkin method. (2nd January 2018) - Álvarez Hostos, J. C.; Bencomo, A. D.; Puchi Cabrera, E. S.; Figueroa Poleo, I. M.
Abstract: The present work has been conducted in order to develop a novel solution for the heat transfer problem during the continuous casting of steel billets and blooms, by using the element-free Galerkin method under a pseudo-transient moving cross-section slice approach. The transport laws, non-linear aspects and boundary conditions of the initial value problem have been specified. A detailed explanation concerning the characteristics inherent to the application of the element-free Galerkin method to this problem has also been provided. The feasibility and suitability of this novel approach has been verified by comparison with the numerical techniques proposed and the results reported by other researchers as well as an analytical solution of a simple 1-D alloy solidification problem. The results have revealed that this technique could be used successfully in the pseudo transient moving cross-section solution of the heat transfer problem involved in the continuous casting of blooms and square billets.